The Influence of Monetary Policy on Foreign Capital Inflows: A Case Study on Sharia Banks Listed on the Indonesian Stock Exchange - Siska Silvia; M. Rasyidin; M. Saleh (SAINTIS Publishing, 2025)
This study aims to analyze the influence of monetary policy on capital flows in Indonesian Sharia banking. Monetary policy plays a crucial role in determining investment attractiveness through exchange rates and inflation, which can influence investor decisions in allocating capital. This research uses a quantitative approach with multiple linear regression analysis to examine the effects of exchange rates and inflation on capital inflows. The data analyzed covers 36 months from January 2022 to December 2024. The results show that exchange rates have a significant partial influence on capital flows in Sharia banking, while inflation does not have a significant partial effect. These findings indicate that investors consider exchange rate stability to be the primary factor when allocating capital in the Sharia banking sector, highlighting the importance of macroeconomic stability for creating a conducive investment climate.